Lagu Nusantara: Android Role Playing Game for Elementary School Music Learning (Journal of Primary Education, 2018)
The decreasing of studentâ€™s interest and motivation in Indonesianâ€™s traditional music learning caused by less varied of the learning process and the lack of studentâ€™s knowledge about Indonesianâ€™s traditional song. The lack of the utilization of gadget like educational games in the learning process also causes the decreasing of studentâ€™s interest and motivation. This study aims to verify the effectiveness of â€œLagu Nusantaraâ€ games through studentâ€™s interest and motivation in the music art learning, especially about Indonesianâ€™s traditional song. The method that used in this study is a quantitative method with the post-test only control group design for an experimental model which supported by the observation of games that used by students. The research subject was 89 elementary students who divided into a control group and experimental group (45 students for the control group and 44 students for experimental group). The result, â€œLagu Nusantaraâ€ as the game is sufficient to promote studentâ€™s interest and motivation in the music art learning process, especially about Indonesianâ€™s traditional song. As supporting data, this research obtained observation data for studentâ€™s interest and motivation which are well in the category (Interest score = 89.44%; motivation score = 87.78%).